Analysis of blunt cerebrovascular injury in pediatric trauma. Issue 6 (December 2019) - Grigorian, Areg; Dolich, Matthew; Lekawa, Michael; Fujitani, Roy M.; Kabutey, Nii-Kabu; Kuza, Catherine M.; Bashir, Rame; Nahmias, Jeffry
Abstract : BACKGROUND: Blunt cerebrovascular injury (BCVI) occurs in <1% of pediatric patients. The two principal screening criteria for BCVI in children are the Utah and McGovern Score with motor vehicle accident (MVA) considered to be a predictor for BCVI. We sought to confirm previously reported risk factors and identify novel associations with BCVI in pediatric patients. METHODS: The Pediatric Trauma Quality Improvement Program (2014–2016) was queried for patients younger than 16 years presenting after blunt trauma. A multivariable logistic regression was used to determine risk of BCVI. RESULTS: From 69, 149 pediatric patients, 109 (<0.2%) had BCVI. The median age was 13 years, and the median Injury Severity Score was 25. More than half the patients were involved in MVAs (53.2%) and had a skull base fracture (53.2%). Factors independently associated with BCVI include skull base fracture (odds ratio [OR], 3.84; 95% confidence interval [CI], 2.40–6.14; p < 0.001), cervical spine fracture (OR, 3.15; 95% CI, 1.91–5.18; p < 0.001), intracranial hemorrhage (OR, 3.11; 95% CI, 1.89–5.14; p < 0.001), Glasgow Coma Scale score of 8 or less (OR, 2.11; 95% CI, 1.33–3.54; p = 0.003), and mandible fracture (OR, 1.99; 95% CI, 1.05–3.84; p = 0.04). Motor vehicle accident was not an independent predictor for BCVI ( p = 0.07). CONCLUSION: In the largest analysis of pediatric BCVI to date, skull base fracture had the strongest association with BCVI. Other associations to pediatric BCVI included cervical spine and mandible fracture. Motor vehicle accident, previously identified to be associated with BCVI, was not an independent risk factor in our analysis. A future multicenter study incorporating newly identified variables in a scoring system to screen for BCVI is warranted. LEVEL OF EVIDENCE: Level IV (Prognostic/Epidemiologic). Abstract : Supplemental digital content is available in the text.